2019
DOI: 10.24875/j.gamo.18000097
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta al tratamiento neoadyuvante en pacientes con cáncer de mama del Departamento de Oncología Médica del Hospital de Clínicas

Abstract: El cáncer de mama es uno de los tumores malignos más frecuentes en mujeres; en Paraguay presenta una alta mortalidad. La quimioterapia neoadyuvante fue introducida para disminuir el tamaño del tumor y volver resecables los tumores considerados irresecables, lo que permite realizar cirugías conservadoras y probar la sensibilidad a la quimioterapia. Material y métodos: Estudio descriptivo, transversal y retrospectivo, con componente analítico. Muestra: 130 pacientes con cáncer de mama que recibieron tratamiento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…This is in accordance with the findings reported by Ruvalcaba-Limón et al [79], who found a weak negative correlation between the percentage of ERs and the clinical response in primary tumors. Similarly, Giménez-Martínez et al [82] reported high chemosensitivity in terms of complete pathological response in tumors with negative hormone receptors and low response rate in luminal tumors. This is important if we consider that our proposal seeks to have an impact in countries with limited funding resources, where molecular tests are not economically viable in public hospitals.…”
Section: Discussionmentioning
confidence: 86%
“…This is in accordance with the findings reported by Ruvalcaba-Limón et al [79], who found a weak negative correlation between the percentage of ERs and the clinical response in primary tumors. Similarly, Giménez-Martínez et al [82] reported high chemosensitivity in terms of complete pathological response in tumors with negative hormone receptors and low response rate in luminal tumors. This is important if we consider that our proposal seeks to have an impact in countries with limited funding resources, where molecular tests are not economically viable in public hospitals.…”
Section: Discussionmentioning
confidence: 86%